Examining links between daily stressor appraisals and C-reactive protein levels in Black and White women: The National Growth and Health Study - Sarah E. Ahmadi; Joanna Y. Guan; Meital Mashash; Elissa J. Hamlat; Mahasin S. Mujahid; A. Janet Tomiyama; Barbara A. Laraia; Elissa S. Epel; Stefanie E. Mayer (Brain, Behavior, & Immunity - Health, 2025)
Background: Racial disparities in health have reached a critical juncture, particularly between Black and White individuals. Inflammation and daily stress have been proposed as biopsychological pathways. However, studies examining links between inflammation and individuals' appraisals of daily stressors—which are modifiable and could be intervention targets—have been limited in diverse populations. This study investigated these associations in a sample of Black and White women. Methods: Midlife women (159 Black, 163 White) were part of a prospective cohort study in which they completed daily evening diaries assessing appraisals of daily stressor demands and coping efficacy (feeling in control, efficacious, resourceful). Participants also provided a fasting blood sample which was assessed for high-sensitivity C-reactive protein (hs-CRP), a systemic inflammatory marker. Multiple linear regression models examined associations between race, daily stressor appraisals, and interactions with hs-CRP, controlling for education, income, and body mass index. Race-stratified models were also examined. Results: The interaction between race and coping efficacy, but not stressor demands, was significantly associated with hs-CRP. Specifically, more positive appraisal of coping efficacy was linked with lower hs-CRP levels in White women (Beta = −0.147, p = .024), but not in Black women (Beta = 0.078, p = .226). Discussion: For White women, greater perceived coping efficacy with daily stressors may buffer stress-related inflammation, providing a promising intervention target. Given the scarcity of daily stress research with diverse samples, we need to better measure and understand these relationships in Black samples and other racial and ethnic groups.